VD_FINDINFO Arrêt / 2024 / 151 vom 9. April 2024 - VD Tribunal cantonal (2024)
COTISATION AVS/AI/APG, GAIN IMMOBILIER, FORTUNE PRIVÉE ET COMMERCIALEDROIT FISCAL | 9 al. 1 LAVS, 9 al. 3 LAVS, 17 RAVS, 23 al. 4 RAVS, 23 RAVS, 27 RAVS